Open habitats in a tropical biodiversity hotspot support pollinator diversity in both protected and unprotected areas. (3rd June 2022) - Balogun, Ibukun; Eluyeba, Olumayowa; Adedoja, Opeyemi; Samways, Michael J.; Polašek, Ozren; Kehinde, Temitope
Abstract: Protected areas (PAs) are vital in the global effort to preserve biodiversity, particularly for disturbance‐intolerant pollinator species in the tropics. As there is little information on the potential of PAs for pollinator conservation in sensitive tropical ecosystems, we assessed here insect pollinator diversity in protected vs. unprotected areas in two vegetation zones in Nigeria, within the West African Guinea Biodiversity Hotspot. We selected two land‐use types based on predominant canopy cover type (open and tree‐shaded habitats) and these were sampled in both protected and unprotected areas of tropical rain forest and savanna vegetation zones. Pollinator composition varied significantly between protected vs. unprotected areas in each vegetation zone, signifying both areas support unique assemblages of insect pollinators. However, pollinator diversity varied according to land‐use type (open vs. shaded habitats) rather than protected area per se, such that pollinators were more abundant and species‐rich in open habitat than shaded habitat. These findings emphasize that beyond the protection of ecosystems, fine scale habitat management promoting the availability of adequate floral resources in natural areas is critical for ensuring conservation of these pollinators in tropical ecosystems. Abstract : As there is little information on the potential of protected areas (PAs) for pollinator conservation in sensitive tropical ecosystems, we assess here insect pollinator diversity in protected vs. unprotected areas in two vegetation zones in Nigeria, within the West African Guinea Biodiversity Hotspot. The results showed that pollinator diversity varied according to habitat type (open vs. shaded habitats) rather than land protection per se, however, pollinator composition was significantly different across land protection categories. These findings emphasize that beyond the protection of ecosystems, fine scale habitat management promoting the availability of adequate floral resources in natural areas is critical for ensuring conservation of these pollinators in tropical ecosystems.